Pembaruan Wewenang Bank dalam Perlindungan Nasabah dari Tindakan Kejahatan Perbankan di Indonesia dengan Prinsip Keadilan - Ichinoty Ramadhani; Aulia Aninda Ektya Putri; Callysta Nabila Nathaniayu; Querida Paraninda Pandan Arum; Tasya Della Sabena; Aulia Rahmawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to evaluate and examine the authority of banks in protecting customers from banking crimes based on Law of the Republic of Indonesia Number 21 of 2011 concerning the Financial Services Authority which still does not fully cover the principle of justice. This research also aims to reconstruct the legal role of banks in providing protection to customers from banking crimes with the principle of justice. The approach method used in this research is a normative legal approach (normative juridical), which refers to legal research that uses analysis of library materials or secondary data. The results show that banking, as an institution that relies on public trust, must provide guarantees to the public. Banks must also be able to maintain the confidentiality of information regarding customers and their savings. Therefore, it is important to continue to supervise and develop banking institutions so that they can function efficiently, fairly, competitively, and can maintain and protect funds deposited by customers.